2022
DOI: 10.1007/s10803-022-05547-6
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in daily life executive functioning between people with autism and people with schizophrenia

Abstract: This is a comparative analysis of everyday executive functioning between individuals with Autism Spectrum Disorder (ASD), Schizophrenia Spectrum Disorders (SSD) and controls using Dysexecutive Questionnaire-Spanish (DEX-Sp), to identify patterns of difficulties. Also we assessed the relationship between EF and adaptive behavior as measured by the Vineland Adaptive Behavioral Scale-II. Common areas of everyday executive functions were established as problematic in individuals with ASD and SSD related to Disinhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
3
2
0
Order By: Relevance
“…More importantly, we found a significant relationship between ASD symptom severity, as measured by the AQ-S and RBQ-2A, and the DLS in the ASD group. Our results support the extensive research on children and adolescents which shows a relationship between ASD symptom severity and adaptive behavior (see Yon-Hernández et al, 2022a ). Therefore, the type of measurement use might be important in detecting whether the severity of symptoms influences adaptive functioning.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…More importantly, we found a significant relationship between ASD symptom severity, as measured by the AQ-S and RBQ-2A, and the DLS in the ASD group. Our results support the extensive research on children and adolescents which shows a relationship between ASD symptom severity and adaptive behavior (see Yon-Hernández et al, 2022a ). Therefore, the type of measurement use might be important in detecting whether the severity of symptoms influences adaptive functioning.…”
Section: Discussionsupporting
confidence: 90%
“…As for the ASD group, they reported that their difficulties in daily executive functioning were significantly greater than those from the SSD group. This pattern is similar to the one reported by Yon-Hernández et al (2022a) where a more exhaustive analysis of the DEX-Sp (our subjective measure) and its subscales was carried out in a larger sample. When analyzing the DEX-Sp subscales in more detail, we found that more difficulties are observed on the disorganization/apathy scale than disinhibition/impulsivity subscale, possibly due to greater role of the former in the daily living skills in ASD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Individuals with ASD continue to develop skills throughout their life, which may help to compensate for their impairments ( 41 ). Also, ASD individuals self-report more difficulties than SCZ individuals related to EF and adaptive behaviors in everyday life situations ( 42 ). Future research should focus more on combination types of assessment such as neuropsychological, and more ecologically valid evaluations of EF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work from Yon-Hernández et al [ 52 ] found that ASD individuals self-report more difficulties than individuals with SSD related to both EFs and adaptive behaviors in everyday life situations. These results differ from the findings of the current study, where we noted relatively more EF problems in SSD than ASD population.…”
Section: Discussionmentioning
confidence: 99%